2017
DOI: 10.1126/science.aag1095
|View full text |Cite
|
Sign up to set email alerts
|

Guanine glycation repair by DJ-1/Park7 and its bacterial homologs

Abstract: DNA damage induced by reactive carbonyls (mainly methylglyoxal and glyoxal), called DNA glycation, is quantitatively as important as oxidative damage. DNA glycation is associated with increased mutation frequency, DNA strand breaks, and cytotoxicity. However, in contrast to guanine oxidation repair, how glycated DNA is repaired remains undetermined. Here, we found that the parkinsonism-associated protein DJ-1 and its bacterial homologs Hsp31, YhbO, and YajL could repair methylglyoxal- and glyoxal-glycated nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 53 publications
6
148
3
Order By: Relevance
“…However, there is no information available yet how DJ‐1 regulates ubiquitination of Sox9. Recently, it has been reported that DJ‐1 has deglycase activity (Richarme et al, ; Richarme et al, ). However, glycation forms protease resistant aggregation (Li, Liu, Sun, Lu, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no information available yet how DJ‐1 regulates ubiquitination of Sox9. Recently, it has been reported that DJ‐1 has deglycase activity (Richarme et al, ; Richarme et al, ). However, glycation forms protease resistant aggregation (Li, Liu, Sun, Lu, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
“…DJ‐1 directly inhibits cell death, and also mediates neuroprotective effects of astrocytes (Junn et al, ; Mullett & Hinkle, ). In addition, DJ‐1 has deglycase activity, by which DJ‐1 prevents and/or repairs glycation‐induced damage of protein and DNA (Richarme et al, ; Richarme et al, ). However, animal models of PD based on mutations in DJ‐1 do not develop PD phenotypes (Chen et al, ), although ischemic and toxin‐induced damage is aggravated in these animals (Kim et al, ), suggesting that DJ‐1 mutations promote PD onset and progression together with brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using knockdown of these enzymes in mice, cell culture, and worms show that these genes play a critical role in avoiding pathologies resulting from the accumulation of α-DC-mediated modification of amino acids or nucleotides (Giacco et al, 2014; Lee et al, 2012; Richarme et al, 2017). The tissue-specificity and sub-cellular localization of the different glyoxalase enzymes are not well-understood.…”
Section: The Maillard Reaction: Initiators Propagators and Chemistrymentioning
confidence: 99%
“…Parkinson's disease protein 7 (DJ‐1/PARK7) contains a network of hydrogen bonds that stabilize sulfinic acid modification at Cys106, presumably inactivating its deglycase activity . DJ‐1 has three conserved cysteines (Cys46, Cys53, and Cys106), but only Cys106 forms a stable sulfinic acid (Figure A and B).…”
Section: Methodsmentioning
confidence: 99%